If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -9 = 9x + 42 Reorder the terms: -9 + -8x = 9x + 42 Reorder the terms: -9 + -8x = 42 + 9x Solving -9 + -8x = 42 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -9 + -8x + -9x = 42 + 9x + -9x Combine like terms: -8x + -9x = -17x -9 + -17x = 42 + 9x + -9x Combine like terms: 9x + -9x = 0 -9 + -17x = 42 + 0 -9 + -17x = 42 Add '9' to each side of the equation. -9 + 9 + -17x = 42 + 9 Combine like terms: -9 + 9 = 0 0 + -17x = 42 + 9 -17x = 42 + 9 Combine like terms: 42 + 9 = 51 -17x = 51 Divide each side by '-17'. x = -3 Simplifying x = -3
| (u-8)(u-4)= | | 9+2(5m-3)= | | 3(x-1)=x+3 | | 2n+1=-31 | | 15y^2+25y+10=0 | | 2x+3(x+4)=12 | | -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 | | y+2=4y+1 | | 113.0=3.14r^2 | | n=-8n-7n | | 1=22 | | 7-4[2-(3y-5)]= | | 2q+369=853 | | x+3.07+x=74.87 | | 3(1t-7)=6t | | 7y-26=-61 | | 5x+2x=65 |